2016
DOI: 10.1002/adma.201600812
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Buckling to Design Architected Materials that Exhibit Effective Negative Swelling

Abstract: Inspired by the need to develop materials capable of targeted and extreme volume changes during operation, numerical simulations and experiments are combined to design a new class of soft architected materials that achieve a reduction of projected surface-area coverage during swelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(86 citation statements)
references
References 53 publications
1
84
1
Order By: Relevance
“…The bending originates from the different cross-linking densities resulting from different exposure doses, leading to different levels of volume shrinkage of the constituents during development. Notably, this shrinkage leads to an overall expansion of the metamaterial sample – in agreement with the operation principle28. This pre-bending also directly evidences that the two components actually have different properties.…”
Section: Resultssupporting
confidence: 82%
“…The bending originates from the different cross-linking densities resulting from different exposure doses, leading to different levels of volume shrinkage of the constituents during development. Notably, this shrinkage leads to an overall expansion of the metamaterial sample – in agreement with the operation principle28. This pre-bending also directly evidences that the two components actually have different properties.…”
Section: Resultssupporting
confidence: 82%
“…Buckling induces an effective negative swelling ratio in this structure. Reprinted with permission from Liu et al [165]. Copyright 2016 by John Wiley & Sons.…”
Section: -10 / Vol 69 September 2017mentioning
confidence: 99%
“…Beyond the instability threshold, rapid and dramatic changes of the structural geometry occur, and a careful design of the initial architecture may lead to the formation of new and homogeneous periodic patterns [159][160][161][162]. Interestingly, it has been recently shown that such dramatic geometric rearrangements induced by instabilities can be exploited to rapidly tune the macroscopic response and functionalities of the structures [22,34,[163][164][165][166][167][168][169][170][171][172][173][174].…”
Section: Instability-driven Pattern Formationmentioning
confidence: 99%
See 2 more Smart Citations